Encyclopedia of global warming - Dutch, Steven I.; Gale Group (Pasadena, California Salem Press, 2010)
Provides comprehensive coverage of the questions of global warming and climate change, including scientific descriptions and explanations of all factors, from carbon dioxide to sunspots, that might contribute to climate change.
v. 1. Abrupt climate change-Energy Policy Act of 1992 -- v. 2. Energy resources-Organization of petroleum exporting countries -- v. 3. Oxygen, atmospheric-Younger Dryas. Appendixes. Index.
Electronic reproduction.
Keywords: Global warming -- Encyclopedias; Climatic changes -- Encyclopedias; Electronic books